Tumor Induced Osteomalacia: A Rare Case of Metabolic Bone Disease, often Underdiagnosed or Misdiagnosed - Wasti, KP; Nepal, R; Malla, D; Karki, BB (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: We present a case of a 42-year female with Tumor induced osteomalacia (TIO) who presented with multiple fragility fractures and decrease in height. The duration from symptom onset to the diagnosis and treatment was 5 years. It is imperative to keep TIO as differential in patients with chronic hypophosphatemia and osteomalacia.